2011
DOI: 10.1007/s00066-011-2250-6
|View full text |Cite
|
Sign up to set email alerts
|

Hematogenous metastases in patients with Stage I or II endometrial carcinoma

Abstract: Hormonal therapy and chemotherapy play a major role in the palliative management of patients with hematogenous metastases from endometrial carcinoma to the liver, lungs, and bones. Radical treatment in patients with metastases to the lung or liver consists of resection of the metastasis combined with chemo- and/or hormonotherapy for metastases to the bones treatment consists of radiotherapy + chemotherapy, for metastasis to the brain treatment consists of resection combined with radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 53 publications
0
15
0
1
Order By: Relevance
“…There are several patterns of metastatic spread from EC, including intra‐abdominal spread and lymph node involvement; however, distant organ metastasis involving the lungs, liver, brain, or bone is considered a unique situation . Although distant organ metastasis is a rare event in EC, it has important implications and is associated with substantially shortened survival . Moreover, the specific site of distant metastasis can influence survival for women with EC, and it is important to understand the patterns of metastasis in newly diagnosed cases in order to more accurately predict prognosis and select an appropriate management strategy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several patterns of metastatic spread from EC, including intra‐abdominal spread and lymph node involvement; however, distant organ metastasis involving the lungs, liver, brain, or bone is considered a unique situation . Although distant organ metastasis is a rare event in EC, it has important implications and is associated with substantially shortened survival . Moreover, the specific site of distant metastasis can influence survival for women with EC, and it is important to understand the patterns of metastasis in newly diagnosed cases in order to more accurately predict prognosis and select an appropriate management strategy.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] Although distant organ metastasis is a rare event in EC, it has important implications and is associated with substantially shortened survival. 6,7 Moreover, the specific site of distant metastasis can influence survival for women with EC, and it is important to understand the patterns of metastasis in newly diagnosed cases in order to more accurately predict prognosis and select an appropriate management strategy.…”
Section: Introductionmentioning
confidence: 99%
“…These diseases exhibit a significant potential for distant metastases, even at early stages, as evidenced by the identification of bone metastases in cervical cancer patients with suspected clinical stage 2B disease. In a study of hematogenous metastases in patients with FIGO Stage 1 or 2 endometrial carcinoma, 134 metastatic sites were identified in a total of 110 patients, and bone involvement was observed in 23 patients [16]. …”
Section: Discussionmentioning
confidence: 99%
“…Hysterectomy and bilateral salpingo-oophorectomy alone or in association with pelvic and para-aortic lymphadenectomy allow a successful treatment in a majority of cases, depending on the stage of the disease. In the event of poor prognostic factors, adjuvant therapies, such as chemotherapy and/or radiotherapy, are associated to surgery [14,15]. Even though some evidence suggests that age is not an independent prognostic factor, older patients seem to present a poorer prognosis.…”
Section: Treatment Of Advanced Ecmentioning
confidence: 99%